Mechanical Properties of Short Random Oil Palm Fibre Reinforced Epoxy Composites - Mohamed Yusoff, Mohd Zuhri; Salit, Mohd Sapuan; Ismail, Napsiah; Wirawan, Riza (2010)
This paper presents the study of mechanical properties of short random oil palm fibre reinforced epoxy (OPF/epoxy) composites. Empty fruit bunch (EFB) was selected as the fibre and epoxy as the matrix. Composite plate with four different volume fractions of oil palm fibre was fabricated, (5 vol%, 10 vol%, 15 vol% and 20 vol%). The fabrication was made by hand-lay up techniques. The tensile and flexural properties showed a decreasing trend as the fibre loading was increased. The highest tensile properties was obtained for the composite with fibre loading of 5 vol% and there were no significant effect for addition of more than 5 vol% to the flexural properties. Interaction between fibre and matrix was observed from the scanning electron microscope (SEM) micrograph.